Problem of the coconut mite Eriophyes guerreronis Keifer in the coconut groves of Trinidad and Tobago - Griffith, Reginald (Ministry of Agriculture, Lands and Food Production Port of SpainTT)
Outlines characteristics of coconut mite and economic effects of its distribution. Describes movement of mite in Trinidad and Tobago by water, wind, and insect dispersal. Discusses methods of control and eradication using a systematic acarricide and vamidothion.